Mexican crisis and its regional implications. - FAUST, Joerg (1995)
Puts forward the thesis that the reasons for the Mexican economic crisis are rooted in economic failings not attributable to the neo-liberal doctrine of development. Examines the implications of the crisis for Latin American subregionalism, and for NAFTA and its possible enlargement into a free trade area for the entire hemisphere.